2019
DOI: 10.1007/s10973-019-08766-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body cryostimulation impact on blood serum thermal denaturation profiles of cross-country skiers

Abstract: Blood plasma and serum are important diagnostic materials as they clearly reflect an individual’s metabolism. The study has evaluated the effect of whole-body cryostimulation (WBC) on the blood serum of professional cross-country skiers. The experiment involved eight athletes (two women and six men) who underwent a series of ten WBC treatments. Aqueous solutions of human blood serum samples before WBC procedures, after one treatment and after a series of ten treatments were measured by means of differential sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It should be also noted that none of the participants was overweight. In our earlier study [63], a decrease of % fat content after 10 WBC was found but mainly for participants with the low level of body fat mass.…”
Section: Resultsmentioning
confidence: 64%
“…It should be also noted that none of the participants was overweight. In our earlier study [63], a decrease of % fat content after 10 WBC was found but mainly for participants with the low level of body fat mass.…”
Section: Resultsmentioning
confidence: 64%
“…The thermal denaturation of the proteins contained in the blood sera is observed in serum DSC profile as complex endothermic transition. At first sight, at least two or three peaks can be distinguished in this transition for healthy people, depending on the serum proteome and the solvent used [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Mean DSC curves of aqueous solutions of human blood sera samples collected from participants of our study at three time points (before sauna treatments, after 1 sauna treatment and after 10 sauna treatments) are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) has found wide application in medical and biological sciences [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Attempts to use the DSC method for clinical purposes have been made for several years [15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBC procedures have a vast scope of application; apart from post-traumatic rehabilitation of injured locomotor system, they are also in the training of professional athletes. A significant factor is a decrease in the intensity of post-traumatic pain and edema, to which athletes are especially exposed during their training, as well as a subjective improvement in general condition and better exercise tolerance [ 2 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%